Allgemeine Wirkfaktoren in ambulanter Ausbildungstherapie: Validierung der deutschen Fassung des SACiP - Call, Manuela; D'Errico, Louisa; Bents, Hinrich; Mander, Johannes (Psychotherapeut, 2018)
ObjectiveThe aim of the current study was the replication of the results of the validation of the Scale for the Multiperspective Assessment of General Change Mechanisms in Psychotherapy (SACiP). So far, the SACiP has been validated only for inpatient therapy. The aim was to replicate the results for the setting of outpatient training therapy. Hence, a brief and conceptually broad instrument should become available in the context of individual training therapy that has been previously validated only for the inpatient setting.Material and methodsParticipants of the study were 870 outpatients. The SACiP and relevant outcome measures were completed by 500 participants in the early therapy phase and 666 participants in the late therapy phase.ResultsUsing confirmatory factor analyses the factor structure of the original instrument for both the patient and therapist perspectives could be replicated. The subscales had good to excellent internal consistencies and showed significant even if only small associations with symptom reduction.ConclusionThe current replication study showed that the SACiP is suitable for the efficient assessment of general change mechanisms in outpatient training therapies. The patient and therapist versions of the SACiP can be applied to closely monitor the individual therapy process.
Gesehen am 15.03.2019